AN OUTER APPROXIMATION METHOD UTILIZING THE RELATION OF CONNECTIONS AMONG VERTICES FOR SOLVING A DC PROGRAMMING PROBLEM - Yamada, S.; Tokushige, Y.; Tanaka, T.; Tanino, T. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, we improve the outer approximation method proposed by Tuy [10] for solving a dc programming problem. The improved algorithm has the global convergence by generating a sequence of polytopes approximating a compact convex set from outside. Moreover, by incorporating a procedure for calculating the vertex sets utilizing the relations of connections among vertices by edges, the improved algorithm can calculate an approximate solution effectively.